One thing I do know: John 9, Citizen Ruth, and bodily autonomy - Torgerson, Laura Jean (2023)
In John 9, an unnamed man born blind receives sight only to find himself at the center of various controversies and theological questions that concern identity and belonging. In the center of the swirling debates, the newly sighted man does not give the theological and political answers his interlocutors demand. He insists instead on his physical well-being as the centrally relevant reality. This article reads John 9 intertextually with the 1996 film Citizen Ruth, in which a pregnant White woman similarly finds herself in the center of a vigorous debate about abortion and often baffles the ideologically motivated groups that seek to persuade her to their side. She, too, insists on her right to act in her own best interests as she perceives them and is subjected to intrusive questions, social stigma, and shame. This reading finds sources for an ethic that centers human flourishing, bodily autonomy, and the ability of marginalized individuals to say what they know to be true about themselves. Such an ethic is surely needed for such a time as this, when fierce ideological debates and political manipulations place marginalized bodies at risk.
Keywords: John 9; health care providers; Embodiment; bodily autonomy; abortion rights